Rat Race Redux: Adverse Selection in the Determination of Work Hours in Law Firms - Landers, Renée M.; Rebitzer, James B.; Taylor, Lowell J. (American Economic Review, 1996)
This paper describes an organizational setting in which professional employees are required to work inefficiently long hours. The focus of our investigation is large law firms. The income sharing that characterizes legal partnerships creates incentives to promote associates who have a propensity to work very hard. Law firms use indicators of this propensity–especially an associate's record of billable hours–in promotion decisions. Reliance upon work hours as an indicator leads to a "rat-race" equilibrium in which associates work too many hours. We find evidence in support of this conclusion with data we collected from two large law firms.